(untitled) (Journal of Hama University, 2019)
This investigation was carried out in Al-Ghab, Hama, Province during the two agricultural seasons 2016 and 2017. The experiment was conducted in an open field. This research included hybrid Natasha F1, was grafted on rootstocks of pumpkins ,Forza F1,Jawad F1 and (Lagenaria siceraria. Mol). Vaccination increased the weight of the fruits, and the results of the study showed that the plants of the muskmelon hybrid Natasha F1, grafted on rootstocks of Forza F1 gave the highest total yield (8.69)ton/dunum, and achieved an increase of productivity (91.83%), compared to the control. The grafted plants showed an increase in the firmness of the fruits, which was proportional to the increase in the thickness of the crust, and the thickness of the fleshy wall (pulp). The grafted plants on (Lagenaria siceraria. Mol) gave the highest firmness (2.14 kg / cm2) and the thickness of the crust (1.26) cm, and the fruits of the plants grafted on the pumpkin (Lagenaria siceraria. Mol) increased the thickness of the fleshy wall (pulp) (4.67 cm).The proportion of soluble solids and total sugars in the fruit of the grafted plants was less than the control, while the quantity of vitamin C in the fruit of the grafted plants was higher than the control.